The mental and moral aspects of manual training - Conner, Gertrude Matilda (My University, 1905)
Introduction: Since 1870 the rapidity of the development of the industrial education has been very marked. There has been a rapid increase in the special schools. The introduction of Manual Training seemed to arise about the same time in England and the United States. In England it was, apparently, the result of the World's Fair of 1851. Here it was shown that commercial supremacy was based on industrial superiority. In the United States it originated in Boston in 1870, an outcome of the English movement. Since that time great progress has been made, and is still being made for the introduction of Manual Training in schools and colleges, until at the present time even Summer schools are being opened .for certain lines of Manual Training. Every year hundreds of young people come, seeking this line of work, and the question arises, how may they be benefited mentally and morally. In the Manual Training School, the foundation of intelligence and skill is laid, and the pupil learns not the principle of one, but of many trades. Get the student to love work, next, let him find the work for which he is best suited. Assist him in what he can do best. Teach him it is just as honorable to be a greasy mechanic, as a cleanly business man, that the field of production is as broad, and even broader, than the field of commerce. The Kindergarten might be called the first step in industrial training. There are the small children of our cities who grow up around us in idleness and sin. Some are sinful by nature, while others are so full of nervous activity that they cannot be idle, and "Satan finds mischief for their idle little hands". Give the rich and poor children the same chance, place them in the Kindergarten, there they are so busy they have no time to learn bad language, or to think bad thoughts.
Citation: Conner, Gertrude Matilda. The mental and moral aspects of manual training. Senior thesis, Kansas State Agricultural College, 1905.
Morse Department of Special Collections
Keywords: Manual Training School; Kindergarten; Grammar; Theses